Pengaruh faktor kontekstual dan sosio demografi terhadap minat berwirausaha pada mahasiswa di Sekolah Tinggi Ilmu Ekonomi Riau Pekanbaru - Anita, Dira Fitri; Ganarsih, Raden Lestari; Wasnury, Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The objective of this research is to identify influence contextual factors and social demographic to the interest for entrepreneurship at School Of Economics Riau In Pekanbaru. The population of this research is 1,511 students majoring in management. A technique called proportional random sampling is used. From this technique, about 100 students in majoring management are concluded. Also, the method of collecting data is using the questionnaire, whereas dual linear regression technique is used as data analysis by using SPSS program. The research found in leads to a result that the contextual factors and social demographic is positively affected significant by interest in entrepreneurship. An F-Test is formulated and thus, can be concluded that the variable of contextual and social domographic are positively and significantly related to interest in entrepreneurship. Adjusted R2 of 0.188 indicates that independent variable stimulateunously affects 18,8% on the interest for entrepreneurship at School Of Economics Riau In Pekanbaru. The rest 81,2% is explained by the other factors to this research.Keywords: Contextual Factors, Interest For Eneterpreneurship and Social Demographic